2018
DOI: 10.1021/acssuschemeng.8b02698
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Valorization of Furfural to Maleic Acid

Abstract: Maleic acid (MA) is a platform chemical used for various industrial processes. In this study, a new electrochemical oxidation method that can convert furfural, which is one of the most important C5 platform chemicals derived from cellulosic biomass, to MA is reported. This method can produce MA in aqueous media under ambient temperature and pressure without the use of oxidizing agents. The use of acidic media, which promotes opening of the furan ring during oxidation, was critical for the formation of MA. PbO2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 28 publications
1
72
0
2
Order By: Relevance
“…In order to promote the formation of electrochemical valorization of furfural to maleic acid, which requires an eightelectron oxidation pathway and opening of the furan ring, Choi and colleague investigated electrochemical oxidation of furfural in acidic media by employing PbO 2 as the anode (Figure 5a). [69] PbO 2 is stable in acidic media under strongly oxidizing potentials, while not being catalytic for water oxidation. The use of acidic media, which promotes opening of the furan ring during oxidation, was critical for the formation of maleic acid.…”
Section: Coupling Her With Aldehyde Oxidation Reactionsmentioning
confidence: 99%
“…In order to promote the formation of electrochemical valorization of furfural to maleic acid, which requires an eightelectron oxidation pathway and opening of the furan ring, Choi and colleague investigated electrochemical oxidation of furfural in acidic media by employing PbO 2 as the anode (Figure 5a). [69] PbO 2 is stable in acidic media under strongly oxidizing potentials, while not being catalytic for water oxidation. The use of acidic media, which promotes opening of the furan ring during oxidation, was critical for the formation of maleic acid.…”
Section: Coupling Her With Aldehyde Oxidation Reactionsmentioning
confidence: 99%
“…It has been reported that MA could be produced from electrocatalytic oxidation, but toxic PbO 2 was employed as the electrode and the MA yield was only 65.1%. 10 Thus, robust and low-cost electrode materials are still highly desirable for the synthesis of MA via electrocatalytic oxidation of lignocellulose-derived furan compounds into MA.…”
Section: Introductionmentioning
confidence: 99%
“…Maleic acid is an intermediate of chemical synthesis that is widely applied in medicines, pesticides, and foods [12]. Maleic acid cannot be produced biochemically, and it is industrially derived from the oxidation of butane, butadiene, or 2 of 11 benzene at high temperatures, with catalysts such as vanadium oxides or vanadiumphosphorous [12,13]. To produce about 2 million tons of maleic acid per year, bio-based and eco-friendly feedstock must be developed, and a cost-effective process is required [8].…”
Section: Introductionmentioning
confidence: 99%
“…Energies 2021, 14, 918 2 of 11 benzene at high temperatures, with catalysts such as vanadium oxides or vanadium-phosphorous [12,13]. To produce about 2 million tons of maleic acid per year, bio-based and eco-friendly feedstock must be developed, and a cost-effective process is required [8].…”
Section: Introductionmentioning
confidence: 99%